Hospitals Responsibility For Delivering Authority Of Doctors To Nurses - Adi Nugraha; Hendra Nur Widyasari; Arlene Sanjaya; Riza Ristiana Umami; Aris Prio Agus Santoso (Universitas Duta Bangsa Surakarta, 2022)
ABSTRACT; In health services, hospitals place doctors and nurses as personnel who are most closely related to services to patients, so it does not rule out the possibility of frequent delegation of authority from doctors to nurses for actions taken to patients. In practice, many nurses carry out doctor's orders in the form of medical actions. The task of doctors without clear boundaries with the duties of nurses as nursing care providers, will ultimately have an impact on patient satisfaction in the services of health workers in hospitals. In such conditions nurses and doctors will be very risky to get into legal trouble. The purpose of this study was to determine the hospital's responsibility for the delegation of authority from doctors to nurses, and legal protection for nurses as recipients of delegation of authority. The approach method used in this study is a library research approach with secondary data collection. The nature of this research is prescriptive design, and the data obtained from this research is then analyzed qualitatively. Based on the results of the study, it was found that the hospital's responsibility for the delegation of authority from doctors to nurses, including: conducting guidance and supervision of the act of delegating authority between doctors and nurses, preparing a letter of delegation of authority which is part of the medical record, and fulfilling all the needs that become part of the medical record. the reason for the delegation of authority. Legal protection for nurses as recipients of delegation of authority is divided into 2 (two) parts, namely preventive and repressive efforts. Preventive legal protection, including; prepare, procure, and complete the letter of delegation of authority in writing between doctors and nurses, then carry out the obligations as instructed in the letter of delegation of authority without going outside the limits of authority and reasonableness. Repressive legal protection, including; there is a guarantee from the hospital to the nurse if things happen that are not desirable from the delegation of authority, then there is a responsibility that the hospital can implement towards the delegation of authority from doctors to nurses